El Excentrico, 1967-08-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
August 20, 1967 [20 de Agosto de 1967]. No Volume or issue number. Cover has a portrait of a man with covered eyes, with headline, "Identify Mystery Face Win a De-Luxe Mexican Combination Dinner."